Consumer Knowledge: Its Measurement and Extent - Oxenfeldt, Alfred R. (The Review of Economics and Statistics, 1950)
E FFICIENT operation of a free enterprise system requires that consumers look after their own welfare. Persistent failure of consumers to safeguard their own interests can seriously weaken even the richly endowed economy of the United States. Moreover, consumer ignorance could well be a major cause of the economic privations of the poorest third of the nation. It is universally acknowledged that consumers lack knowledge to some degree. However, no systematic effort has been made to probe the size of this deficiency. No one knows whether most consumers intelligently pursue their self-interest most of the time or whether most of them fail to do so most of the time.